Pembinaan Keluarga Terhadap Pencegahan Stunting Pada Balita di Kelurahan Padang Bulan Medan - Anna Waris Nainggolan; Eka Purnama Sari; Edy Marjuang Purba; Lusiatun Lusiatun; Imarina Tarigan; Iqra Manisah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
In Indonesia, the incidence of stunting among toddlers is still high. The results of the Republic of Indonesia Basic Health Research (RISKESDAS) in 2018 showed that around 30.8% of children under five were stunted. This figure makes stunting in Indonesia a serious problem because the WHO recommendation for the incidence of stunting in children is less than 20%, if the prevalence of stunting is 30-39% then it is categorized as a serious problem. Based on the results of community service activities carried out in the Padang Bulan sub-district, it is known that family knowledge regarding preventing stunting in toddlers is still quite low, so it is necessary to carry out family development towards preventing stunting in toddlers. After the coaching was carried out, it was discovered that there was an increase in the family's knowledge and ability to prevent and reduce the risk of stunting in toddlers. It is hoped that they will form and implement stunting prevention programs for toddlers to increase mothers' knowledge about stunting and parenting patterns for feeding toddlers.